2023
DOI: 10.25165/j.ijabe.20231601.7954
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress and future prospects for mechanized harvesting of fruit crops with shaking systems

Abstract: Mechanized harvesting technologies with shaking systems for fruit industry have been widely investigated and significantly developed over the past several decades which were presented by a large amount of literature. This paper reviews the research and development progress of mechanized harvesting of fruits systematically with a focus on the theoretical study, fruit crop variety, shaking system categories, abscission chemical agents, and their actual applications. Based on the comprehensive review, mechanized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…However, a body of evidence has shown that the current pesticides are ineffective against resistant pests. In addition, there is a great concern regarding the negative impact to the environment with respect to hazards, and the science community is similarly unsettled about the severe side effects on non-target organisms as well as the extravagant price tag [37]. Several reports have shown that the maize weevil affected maize in Southern and Eastern Africa, Central America, and Mexico [17,38].…”
Section: Host Plants and Feedingmentioning
confidence: 99%
“…However, a body of evidence has shown that the current pesticides are ineffective against resistant pests. In addition, there is a great concern regarding the negative impact to the environment with respect to hazards, and the science community is similarly unsettled about the severe side effects on non-target organisms as well as the extravagant price tag [37]. Several reports have shown that the maize weevil affected maize in Southern and Eastern Africa, Central America, and Mexico [17,38].…”
Section: Host Plants and Feedingmentioning
confidence: 99%
“…For different types of sieves, previous researchers have conducted a lot of research on mesh size, screen inclination, distribution law and optimization configuration [13][14][15][16] . Dong et al [17] used discrete element method to explore the law between vibrating screen frequency, amplitude and screen inclination angle in order to obtain the best screening efficiency; Fernandez et al Revealed the flow characteristics of particles through a double-layer banana sieve [18] ; Jiao et al [19,20] studied the optimal configuration relationship between the mesh diameter and the screen inclination angle, revealing the influence of the mesh diameter and the screen inclination on the screening efficiency; Wang et al [21] proposed a shell sieve body.…”
Section: Introductionmentioning
confidence: 99%
“…Some forest fruits are not picked as a result of the decline in rural population (Chen et al, 2019). As a result, it is one of the best ways to increase the level of automated fruit harvesting (Pu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%